Innovative technologies in elite sport & application of sports science technology to enhance sports performance - Lam, A.; Kay, L. K. (Elite Training Seminar Series, 2017)
Athletes always push themselves to be succeed. Modern technology, especially in data collection, processing and visualization, may facilitate the involvement about scientific approach in elite sport training. The Sport Biomechanics and Technology Centre of the Hong Kong Sports Institute has been working closely with athletes, coaches as well as sports scientists in acquiring timely and accurate sports performance data, and help them achieve an excellent performance. The speaker will briefly introduce the sports technology services in HKSI, review a number of recent applications and explore the future opportunities of the service.